Effect replacement of soybean meal with the sesame meal as a protein source and adding of phytase enzyme to the diet on production performance and some physiological blood indicators of quail bird in the growth stage - Younis, Duraid Thonnon; Al- Sofee, Khalid Hadi Mustafa (Journal of agricultural, environmental and veterinary sciences, 2021)
The study was conducted in the field of poultry in the Animal Production Department/ College of Agriculture and Forestry/ University of Mosul, aimed to study the effect of replacing soybean meal(SBM) with sesame meal(SSM) as a protein source and adding the phytase enzyme to the diet on productive performance and some physiological blood indicators of quail birds in the growth stage. five hundred quail birds were used at the age of one week unsexed and distributed randomly into ten treatments, each treatment was five replicates, ten birds for each replicate, birds reared until 42 days old. The experimental treatments were replacement of SBM with SSM in (0, 25, 50, 75 and 100%) without or with the addition of phytase (300 unit phytase/ kg diet). The results showed that there was no significant effect of replacement the sesame meal at rates that reached (75%) without or with the addition of phytase in the final live weight and weight gain as compared to the negative control (0% SSM without phytase). Significant improvement (P≤0.05) in feed conversion ratio for the two replacement treatments (50 and 75% SSM without phytase) compared to the negative control and a significant improvement for the replacement treatments (25, 50 and 75% SSM with addition of phytase) compared to the negative and positive controls. And there was a significant improvement in the production index in favor of the two replacement treatments (50 and 75% SSM with addition of phytase) as compared to the negative control only. The results showed a significant deterioration when replacing the sesame meal instead of soybean meal by (100%) without or with the addition of phytases in live body weight, weight gain, relative growth rate and production Index as well as a decrease in the percentage abdominal fat compared to the negative and positive controls and a decrease in %PCV as compared to only negative control. The replacement treatment (100% SSM without phytase) recorded a significant increase in dressing percentage as compared to the two controls. The results of this study showed the possibility of replacing soybean meal with sesame meal by up to 75% without or with the addition of phytase enzyme to the diets of quail in the growth stage without any negative effects on production performance.
Keywords: quail bird; soybean meal; sesame meal; phytase enzyme